Advances in Industrial Design Engineering - Coelho, Denis A. (IntechOpen, 2013)
A fast paced changing world requires dynamic methods and robust theories to enable designers to deal with the new product development landscape successfully and make a difference in an increasingly interconnected world. Designers continue stretching the boundaries of their discipline, and trail new paths in interdisciplinary domains, constantly moving the frontiers of their practice farther. This book, the successor to "Industrial Design - New Frontiers" (2011), develops the concepts present in the previous book further, as well as reaching new areas of theory and practice in industrial design. "Advances in Industrial Design Engineering" assists readers in leaping forward in their own practice and in preparing new design research that is relevant and aligned with the current challenges of this fascinating field.